Driving Organizational Citizenship Behavior in Healthcare: The Synergistic Roles of Commitment, Motivation, and Job Satisfaction - Rizal Maulana; Sentot Imam Suprapto; Atik Setiawan Wahyuningsih (KHD Production, 2026)
Organizational Citizenship Behavior (OCB) is critical for enhancing organizational effectiveness in healthcare settings, yet suboptimal levels persist in many hospitals. This study examined the influence of organizational commitment, work motivation, and job satisfaction on OCB among employees at RS Mata Undaan Surabaya, Indonesia, a specialized ophthalmology referral hospital. Using a quantitative cross-sectional survey design, data were collected from 200 randomly selected employees through structured questionnaires. Multiple linear regression analysis was employed to assess both partial and simultaneous effects of the independent variables on OCB. Descriptive analysis revealed that organizational commitment, work motivation, job satisfaction, and OCB were all at good levels. Regression results indicated that organizational commitment (β = 0.274, p < 0.001), work motivation (β = 0.273, p < 0.001), and job satisfaction (β = 0.189, p = 0.001) each exerted a positive and significant partial effect on OCB. Simultaneously, these three variables significantly predicted OCB (F = 64.997, p < 0.001), explaining 49.1% of the variance (Adjusted R² = 0.491). These findings indicate that OCB emerges from the synergistic interaction of positive work attitudes. Hospital management should implement integrated human resource strategies that simultaneously strengthen organizational commitment, enhance work motivation, and improve job satisfaction, thereby fostering voluntary employee behaviors that ultimately improve service quality and organizational performance in specialized healthcare settings.